Global history, globally research and practice around the world - Beckert, Sven (London Bloomsbury Academic, 2018)
"Global history has become one of the most dynamic fields within the discipline of history. The debates surrounding this enormously productive scholarship, however, have remained rather provincial in scope. [This book] addresses this by surveying the state of global history in different world regions"--Back cover.
Includes bibliographical references and index.
Keywords: World history; History -- Methodology; History -- Philosophy; Globalization -- History